Increased Association Between Endometriosis and Endometrial Cancer: A Nationwide Population-Based Retrospective Cohort Study. Issue 3 (March 2015) - Yu, Hann-Chin; Lin, Chun-Yi; Chang, Wei-Chiao; Shen, Biing-Jiun; Chang, Wei-Pin; Chuang, Chi-Mu
Abstract : Objective: Association between endometriosis and ovarian cancer has been well established. Nonetheless, endometriosis may also be associated with endometrial cancer because of shared etiological mechanisms of both estrogen stimulation and chronic inflammation; however, the association between these 2 disorders has rarely been investigated. Methods: The National Health Insurance Research Databases in Taiwan were retrieved and analyzed. The case cohort consisted of patients with a diagnosis of endometriosis between January 1997 and December 2000 (N = 15, 488). For the construction of control cohort, 8 age- and sex-matched control patients for every patient in the case cohort were selected using a random sampling method (n = 123, 904). All subjects were tracked for 10 years from the date of entry to identify whether they had developed endometrial cancer. The Cox proportional hazards regression model was used to evaluate 10-year event occurrence of endometrial cancer. Results: During the 10-year follow-up period, 392 participants developed endometrial cancer, with 104 (0.7%) distributed in the case cohort and 288 (0.2%) in the control cohort. Multivariable Cox regression modeling demonstrates a higher risk for developing endometrial cancer in the case cohort than in the control cohort (adjusted hazard ratio [aHR], 2.83; 95% confidence interval [CI], 1.495.35; P < 0.01). Age at diagnosis of endometriosis shows a moderator effect: when 40 years or younger, the risk for developing endometrial cancer was comparable between the case cohort and the control cohort (aHR, 1.42; 95% CI, 0.55–3.70; P = 0.226), whereas when older than 40 years, the risk for developing endometrial cancer was higher in the former group than in the latter group (aHR, 7.08; 95% CI, 2.33–21.55; P = 0.007). Conclusions: Patients diagnosed with endometriosis may harbor an increased risk for developing endometrial cancer in their later life. Closer monitoring is advised for this patient population.